Toron Tana Tradition In Bangkalan: Between The Priyayi And The Common People - Tussa’banniya, Nabila; Has Wildan, Adam; Br Siregar, Wahidah Zein (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to examine the symbolic meaning and differences in the implementation of the Toron Tana tradition in Madurese society, especially in Bangkalan, by highlighting the differences between the priyayi and ordinary people. The scope of the study includes the symbolic aspects of rituals, the social structure of the tradition actors, and the function of tradition in maintaining the identity and social cohesion of the community. The method used in this study is a qualitative method with a descriptive approach. Data were obtained through interviews with local people, as well as literature studies of relevant references. Data analysis used Émile Durkheim's structural functionalism perspective to understand the social function of the Toron Tana tradition in the context of Madurese society. The results of the study show that although there are differences in the form and excitement of the implementation between the priyayi and ordinary people, the core meaning of the tradition is maintained. This tradition functions as a medium for transmitting cultural and spiritual values, strengthening social solidarity, and reproducing social structures continuously. The conclusion of this study confirms that the Toron Tana tradition is not only a cultural heritage, but also an important instrument in maintaining social integration and the collective identity of the Madurese community amidst the dynamics of changing times.